Application Of Problem Based Learning Model Using Education For Sustainable Development Context In Improving Critical Thingking Ability For Junior High School Students At Heat Theory - Lutfianis, Jenit Anggiani; Chandra Wijaya, Agus Fany; Purwanto, Purwanto (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2020)
Indonesia ranks 6th from the bottom based on four annual studies Trends in International Mathematics and Science Study (TIMSS) in 2015. Based on the results of the TIMSS and PISA, it was said that Indonesian students only mastered low-level questions and lacked high-level questions (HOTS) which included requiring students to think analytically, creatively and critically. Therefore, this study aims to improve students critical thinking skills with the Problem Based Learning model using the education of sustainable development (ESD) context on the heat theory. This study used a one group pretest-posttest design with a sample of 31 students from one of junior high schools in Bandung city. The instrument used was a critical thinking ability test and sustainability awareness profile questionnaire. The acquisition of <g> shows the ability to think critically: Provide a basic explanation of 0.72; build basic skills 0.69; concluded 0.69; make further explanation 0.47; and set the strategy and tactics 0.38. Obtaining sustainability awareness questionnaire 63.33% with the category “practice that are done” based on this, it can be concluded that the problem based learning model using ESD context can be used to improve students' critical thinking skills.